(untitled) (Research, Society and Development, 2022)
Cleft lip and palate (CLP) are the most frequent craniofacial anomalies that affect human beings, and may affect the upper lip, nose and palate. Its etiology is linked to a multifactorial origin, comprising genetic and environmental factors. Dental anomalies are frequent in CLP patients, and can be observed: supernumerary teeth, tooth agenesis, microdontia, enamel defects, delay in tooth formation and eruption, among others. The role of the dental surgeon is fundamental in a multidisciplinary team to establish early diagnosis and adequate treatment for this type of patient. The aim of this study is to describe the most common dental alterations in patients with CLP, through a systematic review of the literature.